2021
DOI: 10.3389/fneur.2021.645729
|View full text |Cite
|
Sign up to set email alerts
|

Novel Volumetric and Surface-Based Magnetic Resonance Indices of the Aging Brain – Does Male and Female Brain Age in the Same Way?

Abstract: Introduction: Novel post-processing methods allow not only for assessment of brain volumetry or cortical thickness based on magnetic resonance imaging (MRI) but also for more detailed analysis of cortical shape and complexity using parameters such as sulcal depth, gyrification index, or fractal dimension. The aim of this study was to analyze changes in brain volumetry and other cortical indices during aging in men and women.Material and Methods: Material consisted of 697 healthy volunteers (aged 38–80 years; M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 47 publications
7
31
2
Order By: Relevance
“…In particular, we found reduction in the superior-frontal, isthmus-cingulate and pars orbitalis regions within males and regions such as inferior-parietal, pars triangularis and paracentral within females. Most of these sex-specific regions were in concordance with previous studies (Armstrong et al, 2019; Podgórski et al, 2021). The mechanisms underlying these sex-specific brain aging differences are not well-known.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, we found reduction in the superior-frontal, isthmus-cingulate and pars orbitalis regions within males and regions such as inferior-parietal, pars triangularis and paracentral within females. Most of these sex-specific regions were in concordance with previous studies (Armstrong et al, 2019; Podgórski et al, 2021). The mechanisms underlying these sex-specific brain aging differences are not well-known.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, large-scale brain age studies have demonstrated its adequacy (Bashyam et al, 2020; de Lange et al, 2019; de Lange, Barth, et al, 2020; Kaufmann et al, 2019). As it has been shown that there are sex-related trajectories in normal aging (Podgórski et al, 2021), we trained separate models for females and males. For each model, we first performed Bayesian parameter optimization based on a cross-validation scheme with ten folds and ten repeats per fold using the FreeSurfer volumes and thickness of the UK BioBank as input.…”
Section: Methodsmentioning
confidence: 99%
“…30 Sex-based differences in CSF volume, however, have not been rigorously evaluated, although recent studies have suggested that adult females may have lower CSF volumes. 31 Lower CSF volumes among girls as compared to age-matched boys would result in higher concentrations of intrathecal chemotherapy among the former. Finally, boys in our cohort received an extra year of maintenance therapy as compared to girls, including 4 extra intrathecal treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Age‐related dosing has thus been associated with increased therapeutic effect and reduced neurotoxicity 30 . Sex‐based differences in CSF volume, however, have not been rigorously evaluated, although recent studies have suggested that adult females may have lower CSF volumes 31 . Lower CSF volumes among girls as compared to age‐matched boys would result in higher concentrations of intrathecal chemotherapy among the former.…”
Section: Discussionmentioning
confidence: 99%
“…The decline of cognitive function in humans is progressive, usually starting at middle age ( Schönknecht et al, 2005 ). Compared to males, age-related cognitive decline and brain atrophy occur earlier in females ( Yuan et al, 2012 ; Podgórski et al, 2021 ). Women have a higher life expectancy than men, but reported a higher prevalence of dementia ( Corrada et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%